Changes in stem growth rates and root wood anatomy of oriental beech after a landslide event in Hanyeri, Bartın, Turkey - Yaman, Barbaros; Köse, Nesibe; Akkemik, Ünal; Yaman, Barbaros (My University, 2013)
On 19 May 1998, a small-scale landslide occurred near Hanyeri, Bartın, in the western Black Sea region. The purpose of the study is to investigate the changes in stem growth rates and root wood anatomy of oriental beech (Fagus orientalis Lipsky). According to results from 8 years before and after the event year, growth variation in the affected trees is significantly high. In the control trees, growth increases after the event year, and the growth variation is 116.22%; this value is 69.59% in the affected trees. However, the growth variation values for ±11 years are 107.69% and 81.36% in control and affected trees, respectively. Root wood anatomy also revealed a clear response in affected trees after the event year, and ring width on one side of the root showed an abrupt increase.
Keywords: Bitki Bilimleri; Turkey; Fagus sylvatica; growth; stems; roots; Bartin; landslides; wood anatomy